NATIONAL DOMAINS AS METAPHYSICAL OBJECTS OF THE TRANSCENDENTAL INFLUENCE ON THE MYTHICAL AND POETICAL PARADIGM OF THE UKRAINIAN STATE-BUILDING MISSION (on the material of the literature of Ukrainian Diaspora of the 20s-50s) - Слоньовська, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the question of the national domains (Domain of Ukrainian State, Domain of Ukrainian Nation, and also national domains of Language, Family, Culture, Science and Ethnopedagogics, Armed Forces, Art). The peculiarities and contradictions of a colonized and colonialist nation through the metaphysical objects of the transcendental influence on the representatives of different nations are elaborated on the basis of V.Barka’s and I.Dfyrianyi’s prose.